2007
DOI: 10.2174/157489107779561625
|View full text |Cite
|
Sign up to set email alerts
|

An Insight on Targets and Patented Drugs for Chemotherapy of Chagas Disease

Abstract: Chagas disease or American Trypanosomiasis, a parasitic infection typically spread by triatomine bugs, affects millions of people throughout Latin America. Current chemotherapy based on the nitroaromatic compounds, benznidazole and nifurtimox provides unsatisfactory results and suffers from considerable side effects and low efficacy. Therefore, there is an urgent need for new drugs to treat this neglected disease. Over the last two decades, new advances and understanding in the biology and the biochemistry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
17

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 310 publications
0
42
0
17
Order By: Relevance
“…Recently there has been great interest in developing new cruzipain inhibitors as chemotherapeutic targets. As proof of this more than 50% of the 51 patents in the 2000-2006 period aiming at different targets for the treatment of Chagas disease, were cruzipain inhibitors (targets included: ergosterol biosynthesis inhibitors, inhibitors of polyamine and trypanothione formation) (Duschak, 2007).…”
Section: Peptidasesmentioning
confidence: 98%
“…Recently there has been great interest in developing new cruzipain inhibitors as chemotherapeutic targets. As proof of this more than 50% of the 51 patents in the 2000-2006 period aiming at different targets for the treatment of Chagas disease, were cruzipain inhibitors (targets included: ergosterol biosynthesis inhibitors, inhibitors of polyamine and trypanothione formation) (Duschak, 2007).…”
Section: Peptidasesmentioning
confidence: 98%
“…In the past years, the study of compounds isolated from plants has received considerable attention in the search for alternative chemotherapy of parasitic diseases (Serrano et al, 2000) and many natural compounds have been identified as trypanocides (Duschak & Couto, 2007;Guimarães & Faria, 2007). Several extracts from plants of Meliaceae and Rutaceae families have been showed in vitro activity against T. cruzi (Mafezoli et al, 2000;Vieira et al, 2001;Ambrozin et al, 2004;de Mesquita et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in our understanding of the basic biochemistry of T. cruzi have allowed the identification of new specific pathways and novel drug targets for chemotherapy, such as sterol biosynthesis, trypanothione reductase, and cystein protease. 1,[3][4][5][6] This has led to some rationally designed and synthesized candidates for the treatment of Chagas' disease. 4) On the other hand, the use of natural products for the treatment of protozoal infections is well known and long documented.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5][6] This has led to some rationally designed and synthesized candidates for the treatment of Chagas' disease. 4) On the other hand, the use of natural products for the treatment of protozoal infections is well known and long documented. 4) A number of recent works reported the trypanocidal activity of a wide variety of extracts of natural medicines or its constituents.…”
Section: Introductionmentioning
confidence: 99%